Improving sustainability development in energy planning and optimisation. (15th December 2016) - Nemet, Andreja; Klemeš, Jiří Jaromír; Duić, Neven; Yan, Jinyue
Abstract: This special issue of Applied Energy contains articles developed from initial ideas related to the 10th Conference on Sustainable Development of Energy, Water and Environment Systems (SDEWES) held in Dubrovnik, Croatia during September 27 - October 2, 2015. The main focus of the event is the sustainability development joining all required areas for achieving as improving the knowledge on method, policies and technologies as well as dissemination of the results. Overall, 64 extended manuscripts have been invited as candidate articles. After a thorough review procedure, 23 articles have been selected to be published. The topics attained in the focus of this Special Issue include Integration, Optimisation and Analysis of energy systems as well as dissemination of the developed methodology and results obtained.